Crystallization and preliminary X-ray analysis of the human long myosin light-chain kinase 1-specific domain IgCAM3 - Graham, W. Vallen (International Union of Crystallography, 2011)
Myosin light-chain kinase-dependent tight junction regulation is a critical event in inflammatory cytokine-induced increases in epithelial paracellular permeability. MLCK is expressed in human intestinal epithelium as two isoforms, long MLCK1 and long MLCK2, and MLCK1 is specifically localized to the tight junction, where it regulates paracellular permeability. The sole difference between these long MLCK splice variants is the presence of an immunoglobulin-like cell-adhesion molecule domain, IgCAM3, in MLCK1. To gain insight into the structure of the IgCAM3 domain, the IgCAM3 domain of MLCK1 has been expressed, purified and crystallized. Preliminary X-ray diffraction data were collected to 2.0 Å resolution and were consistent with the primitive trigonal space group P2(1)2(1)2(1).